Penanganan Lesi pada Ramp Lesi Meniskus Umum: Perbaikan atau Pengobatan Konservatif: Tinjauan Pustaka - Davidson, Alhoi Lesley; Giarso, Peter (PT Kalbe Farma Tbk., 2025)
Ramp lesions are the most frequent intra-articular injuries associated with anterior cruciate ligament (ACL) ruptures and are often missed during diagnosis. They occur at the meniscocapsular junction of the posterior horn of the medial meniscus and may compromise knee stability. Magnetic resonance imaging (MRI) can identify ramp lesions but has limited sensitivity; therefore, arthroscopy remains the diagnostic gold standard. Treatment options include conservative management for stable tears and surgical repair for unstable or type IV–V lesions. Recent studies show no significant difference in long-term knee stability between repaired and unrepaired lesions; however, repaired lesions demonstrate faster functional recovery. Repair is particularly advised for patients in their productive years, especially athletes or individuals with high physical-activity demands requiring optimal knee stability. Appropriate radiologic evaluation combined with structured postoperative rehabilitation improves clinical outcomes and reduces recurrence. This review summarizes current evidence on the epidemiology, diagnosis, classification, and management strategies for ramp lesions commonly found in association with ACL-related meniscal injuries.